State of Connecticut. Office of Secretary of State, May 21st, 1849. To the Hon. House of Representatives . ([publisher not identified], 1849)
1849 report by the Connecticut Secretary of State to the House of Representatives, regarding the number and grounds for divorce within the various counties in the state during 1844-1849. As part of the report there were several tables listing details regarding grounds, names, etc.